A new method of monitoring the stability of boreholes for methane drainage from coal seams. (15th March 2020) - Niu, Yue; Zhang, Xin; Wang, Enyuan; Li, Zhonghui; Cheng, Zihua; Duan, Xianjun; Li, Hao; Wei, Yanwei; Qian, Jifa; Cai, Guannan; Lin, Song; Li, Bing
Highlights: A new system for the simulation and measurement of borehole deformation is designed. The damage degree of borehole can be calculated by relative pressure of sensor through functional relationship. RFPA software simulation verified the experimental results. Abstract: Methane drainage plays a significant role in the utilisation of clean energy, reducing greenhouse effects, and hazards arising from methane-induced disasters during mining. Drainage boreholes have been applied widely, while stability monitoring is needed to guarantee the effect of methane drainage. At present, there is no effective method and device with which to measure the deformation and failure of drainage boreholes. In view of this problem, the mechanical conditions and failure modes of borehole deformation were analysed. A set of simulation and testing devices and systems were designed to explore a new method for monitoring the deformation and failure of a borehole. Moreover, similar simulation experiments were carried out. From the results, the functional relationship between the degree of damage to a borehole and relative pressure on the sensor in the device was established. Meanwhile, the critical value of the degree of destruction of a borehole was revealed. Moreover, the experimental results were also analysed and verified with by the numerical simulation results from RFPA. This study provided a new engineering application for borehole deformation measurement.